2014
DOI: 10.3109/08958378.2014.965560
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms, lung function decrement and chronic obstructive pulmonary disease in pre-menopausal Indian women exposed to biomass smoke

Abstract: Cumulative exposure to biomass smoke causes lung function decrement and facilitates COPD development even in non-smoking and relatively young pre-menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In this study, none of the children and mothers demonstrated combined defect. Other studies focusing on populations exposed to cookstove emissions in India have found all three patterns of lung‐function impairments among the participants (Dutta & Ray, ; Mukherjee et al, ; Norboo, Yahya, Bruce, Heady, & Ball, ). One limitation in studies obtaining PFTs in the field is the inability to obtain lung volumes using plethysmography techniques.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, none of the children and mothers demonstrated combined defect. Other studies focusing on populations exposed to cookstove emissions in India have found all three patterns of lung‐function impairments among the participants (Dutta & Ray, ; Mukherjee et al, ; Norboo, Yahya, Bruce, Heady, & Ball, ). One limitation in studies obtaining PFTs in the field is the inability to obtain lung volumes using plethysmography techniques.…”
Section: Discussionmentioning
confidence: 86%
“…For example, Patel et al (2017) monitored spatio-temporal PM 2.5 in multiple locations of different types of Indian households using similar cookstoves and fuels, and reported that PM 2.5 levels in the living space and bedroom were comparable to that in the kitchen area, even in bigger households than those that participated in this study. which the 95% CI did not include the null value (OR = 1) are presented ( focusing on populations exposed to cookstove emissions in India have found all three patterns of lung-function impairments among the participants (Dutta & Ray, 2014;Mukherjee et al, 2014;Norboo, Yahya, Bruce, Heady, & Ball, 1991). One limitation in studies obtaining PFTs in the field is the inability to obtain lung volumes using plethysmography techniques.…”
Section: Household Air Pollution-health Associationmentioning
confidence: 99%
“…When their analysis was restricted to lifelong non-smokers, airflow obstruction was also more common in the biomass smoke exposed group (5.2% vs 1.8%, p=0.004). Similarly, Mukherjee et al 27 compared 681 non-smoking women from eastern India who cooked exclusively with biomass (wood, dung and crop residues) with 438 age-matched women from similar neighbourhoods who cooked with liquefied petroleum gas (LPG) and reported that airflow obstruction was diagnosed in 4.6% of biomass users, as compared with only 0.9% of LPG users. In contrast, Obaseki et al 28 reported that there was no association between chronic airway obstruction and the use of firewood or coal for cooking or heating in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Females though limited in number were united by a single cause, exposure to biomass fuel in the form of firewood; this mirrored studies across India and in other developing economies. [1415161718]…”
Section: Discussionmentioning
confidence: 99%